Impact of the COVID-19 pandemic on the digitization of routine pediatric practice in Spain: A nationwide survey study - Martín-Masot, Rafael; Diaz-Martin, Juan J.; Santamaría-Orleans, Alicia; Navas-López, Víctor Manuel (Frontiers in Pediatrics, 2023)
COVID-19 pandemic forced a change in the working dynamics of all healthcare professionals, leading to a sudden introduction of telemedicine. Although until that moment telemedicine applications had been described in the paediatric age, its use was anecdotal. The aim of the present study was to analyse the experience of Spanish paediatricians after the forced digitization of consultations due to the pandemic. A cross-sectional survey-type study was designed to obtain information from Spanish paediatricians about the changes that took place in the usual clinical practice, with the participation of 306 health professionals. Most of them agreed on the use of the internet and social networks during the pandemic, referring to mail or WhatsApp® as usual channels of communication with their patients’ families. There was great agreement between paediatricians that evaluation of newborns after hospital discharge and establishing methodologies that allow childhood vaccination and the identification of subsidiary patients for face-to-face evaluation are necessary although the limitations of lockdown. The idea that telephone and digital consultations have optimized the consultation time and that they will probably continue after the end of the pandemic was generally accepted. No changes in adherence to breastfeeding or start of complementary feeding were referred, but an increase in the duration of breastfeeding and the appearance of frequent hoaxes in social networks in relation to infant feeding were found. It is necessary to analyse the impact of telemedicine in paediatric consultations during the pandemic to evaluate its effectiveness and quality in order to maintain it in routine paediatric practise.